2016
DOI: 10.1080/16070658.2017.1237446
|View full text |Cite
|
Sign up to set email alerts
|

The magnitude and determinants of anaemia among refugee preschool children from theKebribeyahrefugee camp, Somali region, Ethiopia

Abstract: Background: Anaemia is a global public health problem affecting children from both industrialised and developing countries with major consequences for health, social and economic development. Although the burden of anaemia is high among refugee children due to their living conditions, its determinants are not yet clearly identified and documented in Ethiopia. Objective: To assess the magnitude and contributing factors of anaemia among refugee preschool children of the Kebribeyah refugee camp. Methodology: A cr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
20
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(24 citation statements)
references
References 7 publications
3
20
1
Order By: Relevance
“…This study has shown that more than 1 under 5 years children living in the households were independently associated with anemia among children 6 to 59 months of age. This finding is consistent with study done in Damot Sore district, Southern Ethiopia of which more than 1 under 5 children within a household 4 times more likely to be anemic as compared to household with 1 under 5 years 28 and also the finding consistent with a study done in National level of Ethiopia, 9 Debre Berhan, 32 Namutumba district, Uganda, 33 Kebri Beyah Refugee Camp, Somali Region, Ethiopia 34 and study done using EDHS data in Ethiopia. 35 It is implied that the prevalence of anemia among children aged between 6 and 59 months in Ethiopia was higher in the households with more number of children under 5 relative to households with lower number of children under 5, and under 5 children living in households with many siblings of same age category in a low-income setting were subjected to increased competition for resources which results in major child health constraints such as stunting and nutritional deficiencies.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…This study has shown that more than 1 under 5 years children living in the households were independently associated with anemia among children 6 to 59 months of age. This finding is consistent with study done in Damot Sore district, Southern Ethiopia of which more than 1 under 5 children within a household 4 times more likely to be anemic as compared to household with 1 under 5 years 28 and also the finding consistent with a study done in National level of Ethiopia, 9 Debre Berhan, 32 Namutumba district, Uganda, 33 Kebri Beyah Refugee Camp, Somali Region, Ethiopia 34 and study done using EDHS data in Ethiopia. 35 It is implied that the prevalence of anemia among children aged between 6 and 59 months in Ethiopia was higher in the households with more number of children under 5 relative to households with lower number of children under 5, and under 5 children living in households with many siblings of same age category in a low-income setting were subjected to increased competition for resources which results in major child health constraints such as stunting and nutritional deficiencies.…”
Section: Discussionsupporting
confidence: 91%
“…This result is consistent with study done in Ethiopia Demographic Health Survey (EDHS 2016), 4 Western Kenya, 45 Damot Sore district, Southern Ethiopia, 28 Debre Berhan 32 and Kebri Beyah Refugee Camp, Somali Region, Ethiopia. 34 The association of stunting and anemia in children might be due to the households’ food insecurity problems and unstrengthened child health caring capacity both at heath institutions and at household level.…”
Section: Discussionmentioning
confidence: 99%
“…The authors did comprehensively review and meta-analyze the predictors of anemia among the study subjects using nineteen meta-analyzable studies 21 , 23 28 , 34 , 36 , 37 , 40 43 , 45 47 , 49 , 50 from the relevant articles included in the current study. Sex of the children, family educational status, family occupation, family income, residence and helminthic infection were found to be worth reviewing and meta-analyzable.…”
Section: Resultsmentioning
confidence: 99%
“…In Ethiopia, previous studies have linked anemia to factors such as child age, child nutritional status, parents' educational level, and wealth index [11][12][13][14][15]. However, almost all studies used single-level analysis techniques with population groups localized in a specific study area [11,12,14,15]. The Single-level analysis assumes that there is no community effect beyond the characteristics of individuals [16].…”
Section: Introductionmentioning
confidence: 99%